2009
DOI: 10.4103/0377-4929.54986
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cytomorphological and microbiological examination of bile collected by endoscopic cannulation of the papilla of vater

Abstract: Complete microscopic and microbiological examination of bile directly obtained from the common bile duct during endoscopic retrograde cholangiopancreatography yielded good results as fresh samples could be analyzed. It may help in diagnosis of many gallbladder lesions in early stages, thereby reducing the morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…We also observed that majority of the malignant cases had pure cholesterol type of stones and none of these had either brown or black pigment stones hence supporting the previous reports of association of GBC with cholesterol stones. 33,36,37 Our findings are similar to a study from Japan by Kimura et al 38 which revealed that though most common type of stones were of pigmented type, but in patients with GBC cholesterol gall stones are most commonly found. Lorna and Cooke 32 however, recorded association of mixed type of stones with GBC.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that majority of the malignant cases had pure cholesterol type of stones and none of these had either brown or black pigment stones hence supporting the previous reports of association of GBC with cholesterol stones. 33,36,37 Our findings are similar to a study from Japan by Kimura et al 38 which revealed that though most common type of stones were of pigmented type, but in patients with GBC cholesterol gall stones are most commonly found. Lorna and Cooke 32 however, recorded association of mixed type of stones with GBC.…”
Section: Discussionsupporting
confidence: 90%
“…Early culture-based surveys of patients undergoing biliary surgery showed the occasional isolation of Proteus species from the biliary tract (13% of bile samples) (102). P. mirabilis has also been recovered from bile obtained during endoscopic retrograde cholangiopancreatography (ERCP) in 6% of cultured samples (103).…”
Section: Association With Hepatobiliary Diseasementioning
confidence: 99%
“…P. mirabilis may also be present in the human gut microflora (5) and is correlated with the incidence of colitis (6,7). Broth-grown vegetative cells of P. mirabilis are characteristically ϳ2 m long and have a peritrichous distribution of ϳ4 to 10 flagella.…”
mentioning
confidence: 99%